2013
DOI: 10.7567/jjap.52.04cm07
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Sub-Nano-Tesla Magnetic Field by Integrated Magnetic Tunnel Junctions with Bottom Synthetic Antiferro-Coupled Free Layer

Abstract: Arrays of 100×100 magnetic tunnel junctions (MTJs) connected in parallel and series were fabricated. A synthetic antiferro-coupled bottom free layer with a NiFe/Ru/CoFeB structure and MgO tunneling barrier were used to realize a high sensitivity, which is defined as TMR/2H k , where, TMR is the tunneling magnetoresistance ratio and H k is the magnetic anisotropy field of the free layer. To obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…The prepared MTJ multilayer lms were microfabricated into MTJ arrays by photolithography and Ar ion milling. The TMR sensor has a structure in which 74 MTJs with device area of 50 × 50 µm 2 are connected in series to reduce the 1/f noise [29][30][31] and the length of the 74 MTJ array is 6.7 mm. After the microfabrication, the MTJ arrays were annealed using the double annealing process with a magnetic eld of 0.3 T to realize linear output response against the external magnetic eld 32 .…”
Section: Sefs Using Squid-megmentioning
confidence: 99%
“…The prepared MTJ multilayer lms were microfabricated into MTJ arrays by photolithography and Ar ion milling. The TMR sensor has a structure in which 74 MTJs with device area of 50 × 50 µm 2 are connected in series to reduce the 1/f noise [29][30][31] and the length of the 74 MTJ array is 6.7 mm. After the microfabrication, the MTJ arrays were annealed using the double annealing process with a magnetic eld of 0.3 T to realize linear output response against the external magnetic eld 32 .…”
Section: Sefs Using Squid-megmentioning
confidence: 99%
“…Research on the development of such new devices is being performed by collaborations of industry, government, and academia. [87][88][89] …”
Section: Detection Of Biomagnetic Fieldsmentioning
confidence: 99%
“…Based on the crystalline barrier, previous studies demonstrated that optimized MTJs with synthetic antiferromagnetic-free layers could provide high sensitivity to sensing the variations in external magnetic fields [ 21 ]. Moreover, thanks to excellent miniaturization, MTJs can be fabricated for submicrometer-sized devices and connected in a series, which can enhance detectivity to obtain a high signal-to-noise ratio (SNR) [ 22 , 23 ]. These study results suggest that developed MTJs enable us to design sensors with high sensitivity and high spatial resolution for MFL testing applications.…”
Section: Introductionmentioning
confidence: 99%